The Types of Primary Tasks Useful in the Organizational Socialization Process - Chomngam, Pornprom (Journal of Business, Innovation and Sustainability (JBIS), 2022)
This research examined the types of primary tasks useful in the organizational socialization process. Questionnaires were administered to 220 participants who ae permanents employees to obtain the data for this study. Repeated measurement was used to analyze the data. Respondents indicated finding all types of primary tasks useful but were most positive in their assessments of social integration task, followed by role mastery and role clarification, while acculturation are rated as moderately useful. The hypothesis was partially supported. Respondents reported significantly higher levels of social integration than role clarification and acculturation, also reported significantly higher levels of role mastery than role clarification and acculturation. No significant differences are observed with respect to social integration and role mastery, role clarification and acculturation.